Transforming Higher Education
XIV, 204 p.
Keywords: This book carries forward the findings of an international research project, first published in 2000, on the radical higher education reforms introduced since the 1970s. It is based upon documents, statistics and extensive interviews with politicians, institutional leaders and academics from a range of institutions and disciplines in three countries. It is one of only a handful of contemporary comparative studies that combine strong empirical research with theoretical analysis developed within a thematic rather than a country based framework. Drawing together the implications of studies of Sweden, Norway and England in a set of comparative analyses, the authors assess the reforms of the higher education systems on three distinct levels, the state, the institution and the individual. They examine change in government policy, in the leadership and management of higher education institutions and the impact on academic identities and the academic profession.